Plasma and salivary measures of testosterone and cortisol levels in basketball players under various games / training conditions, and nutritional strategies: an updated systematic review - Brini, S.; Clark, C. C. T.; Ouergui, I.; Delextrat, A.; Yagin, F. H.; Muscella, A.; Badicu, G.; Bouassida, A.; Clemente, F. M.; Al-Mhanna, S. B.; Tabnjh, A. K.; Nobari, H.; et al. (Frontiers in Physiology, 2025)
Background: In basketball research, hormonal monitoring has focused almost exclusively on plasma and salivary testosterone and cortisol, as these methods are more practical and accessible for applied sport settings than alternative approaches. Yet, no systematic review recapitulates these two methods together among Basketball players under various (games/training) conditions, and different nutritional strategies.